Homoseksual: Antara Hukum dan Kemajuan Sains (Sains Humanika, 2016)
Homosexuality is a phenomenon that has ling existed in human history. It is became the targer of the study to find the contributing factors to the tennets of the Islamic perspective. The desire of homosexuals to change the physical conditions of a male to femare or vice versa is a good convention for sexual purposes or desore to become a mother or father status. The pace and progress of science and technology has helped homesexuals meet their needs, even if the outcome of these treatments may bring much harm to themselves or those around them. High costs of sex change surgeries caused many homosezual stuck to the nature of adultery and leave a negative impact on health. The purpose of this paper is to understand the factor that cause homosexuality: Between law and science. The method used is a qualitative approach and a library. The findidngs of the study showd that the factors that cause the occurrence of homosexuality no only depend on environmental factors such as parents, peers, social and biological factors, but diet and drugs. There is a lack of research on the different schools of taught concerning the change of gender studies, hence it is has become prevalent in the Muslim community. If this is not handled as soon as possible, it not only gives an image that is not healthy within our communities but aslo undermine the development of Islamic civilization.
Keywords: Homosexual; religious law; science